(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:The current research aims to identify the psychological resilience of educational counselors, and for the purpose of achieving the goal of the research, the researchers used the descriptive approach, and the researchers adopted the psychological resilience scale, in Jasim. For the purpose of statistical analysis(Friborg, Hjemdal, Rosenvinge & Martinussen, 2003).For the measure of psychological resilience, a sample of (400) educational counselors was selected, and the sample was chosen randomly from educational counselors. The two researchers extracted the psychometric characteristics of the scale and used statistical indicators. The research mechanism reached from the results, the researchers recommended a set of recommendations and proposals.